Obesity and government. Issue 5 (October 2016) - Kahan, Scott; Zvenyach, Tracy
Abstract : Purpose of review: Despite much effort, obesity prevalence and disease severity continues to worsen. The purpose of this review is to describe the leading government supported food and nutrition interventions and policies to prevent and address obesity in the USA. The review also summarizes obesity interventions and policies that the government plays a role in, but further development is warranted. Recent findings: The government's role in obesity has largely focused on interventions and policies such as national surveillance, obesity education and awareness, grant-based food subsidy programs, zoning for food access, school-based nutrition programs, dietary guidelines, nutrition labeling, and food marketing and pricing policies. The government has played a lesser role in obesity interventions and policies that provide access to evidence-based obesity care to people affected by the disease. Summary: Given the magnitude of the obesity epidemic, the government should explore multiple evidence-based interventions and policies across prevention and clinical care.